Self-ordered TiO2 quantum dot array prepared via anodic oxidation - Drbohlavova, Jana; Vorozhtsova, Marina; Hrdy, Radim; Kizek, Rene; Salyk, Ota; Hubalek, Jaromir (Nanoscale research letters, 2012)
The template-based methods belong to low-cost and rapid preparation techniques for various nanostructures like nanowires, nanotubes, and nanodots or even quantum dots [QDs]. The nanostructured surfaces with QDs are very promising in the application as a sensor array, also called 'fluorescence array detector.' In particular, this new sensing approach is suitable for the detection of various biomolecules (DNA, proteins) in vitro (in clinical diagnostics) as well as for in vivo imaging.The paper deals with the fabrication of TiO2 planar nanostructures (QDs) by the process of titanium anodic oxidation through an alumina nanoporous template on a silicon substrate. Scanning electron microscopy observation showed that the average diameter of TiO2 QDs is less than 10 nm. Raman spectroscopic characterization of self-organized titania QDs confirmed the presence of an anatase phase after annealing at 400°C in vacuum. Such heat-treated TiO2 QDs revealed a broad emission peak in the visible range (characterized by fluorescence spectroscopy).